Stay Hungry Stay Foolish - Rashmi Bansal (Print Vision Pvt Ltd, 2008)
People who knew entrepreneurship was the Chosen Path. They took the plunge straight after their MBA or after working barely a couple of years. And they persevered until theymade it big! THE OPPORTUNISTS - These entrepreneurs did not plan to take this path but when opportunity knocked they seized it. Their stories go to show that you don't have to be 'born with it', you can develop an entrepreneurial bent of mind at any age. THE ALTERNATE VISION - These individuals are using entrepre-neurship to create social impact. Or as a platform which allows them creative expression.